Eficiência de absorção e utilização de fósforo em batata cultivada in vitro - Castro, Gabriel Y (2009)
Phosphorus (P) restriction to plants is one of major limiting factors for crop productivity. Alternatively to application of P-containing fertilizer, this obstacle to the vegetal production can be surmounted by developing of efficient plants in P-uptake and use. The objective of this work was to verify if there is behavior difference for Puptake and use efficiency and response to P-supply in 22 potato clones (Solanum tuberosum e S. microdontum) cultivated in vitro, as well as to report which characteristics of the plants are related to this ability. Concentrations of 10 and 100% of the concentration of P in standard MS medium were applied. Growth parameters and P-accumulation were determinated and P-uptake and use efficiency indexes in roots, shoot and plant were calculated. A wide behavior variation among tested potato clones for P-uptake and use efficiency was found. Dry matter production and P-accumulation had together a fundamental role to show the differences in Pefficiency among clones. P-use efficiency indexes showed same trend among clones and had an inverse relation with the uptake efficiency. The characteristics of root and shoot length and leaf number had secondary importance to the characterization of Pefficiency, and these were associated with only a few clones classified as efficient. Dry matter and P content distribution between root and shoot was not related with Pefficiency in potato. Moreover, these characteristics corroborate the exposure of the variability among potato clones according to the supply of P. Potato clones were classified using P-use efficiency index under low P and response to P-supply for shoot dry matter production: efficient-responsive: SMIC148-A, SMIB106-7, SMIG227- 2 and Michigan Purple; non-efficient-responsive: SMID040-4RY, SMIF313-3, SMIG145-1 and Macaca; non-efficient-non-responsive: S. microdontum, SMIJ319-7, SMIG274-3, SMIE040-6RY, SMIF212-3, SMIJ461-1 and Asterix; and efficient-nonresponsive: SMINIA793101-3, SMIJ456-4Y, Dakota Rose, SMINIA00017-6, SMINIA90244-1, SMIJ319-1 and SMINIA97145-2. These results are a valuable tool for genetic improvement of potato to P-use efficiency and response to P-supply.